Status of international normalized ratio control and treatment patterns in patients with nonvalvular atrial fibrillation taking vitamin K antagonist with or without antiplatelet therapy: Results from KORAFII registry. Issue 4 (17th June 2019) - Park, Hee‐Soon; Kim, Young‐Hoon; Kim, June Soo; Oh, Yong‐Seog; Shin, Dong‐Gu; Pak, Hui‐Nam; Hwang, Gyo‐Seung; Choi, Kee‐Joon; Oh, Seil; Kim, Jin‐Bae; Lee, Man‐Young; Park, Hyung‐Wook; et al.
Abstract: Background: Studies have shown that the concomitant use of a vitamin K antagonist (VKA) and an antiplatelet (APL) drug increased the bleeding risk and was less effective at preventing ischemic events. This study aimed to investigate the control status of international normalized ratio (INR) and the discontinuation rate of a VKA in patients taking VKA plus an APL drug compared with those taking a VKA alone. Methods: Data were extracted from the KORean Atrial Fibrillation Investigation II registry, a multicenter noninterventional prospective observational study. Nonvalvular atrial fibrillation (NVAF) patients with CHADS2 scores ≥ 1 who newly started (within 3 months) a VKA were enrolled and followed up for 1 year. Results: A total of 866 NVAF patients (mean age, 67.7 years; 60.3% men) without a bleeding history were divided into the VKA+APL (n = 229) and VKA alone (n = 637) groups. During follow‐up, mean INR level was lower in the VKA+APL group than in the VKA alone group (1.7 ± 0.8 vs 1.9 ± 0.9, P  = 0.0005). INR levels were poorly controlled in both groups (66.1% and 64.7%, respectively). Patients in the VKA+APL group more frequently discontinued VKA than patients in the VKA alone group (28.8% vs 24.2%, P  = 0.045). Major causes of VKA discontinuation were uncontrolled INR level and patient dissatisfaction or concerns. Conclusions: The conditions of NVAF patients were inadequately controlled with VKA with or without an APL. These findings suggest that other antithrombotic treatment options are warranted in NVAF patients to achieve INR control.